Analysis of Reading Comprehension Questions Based on Higher Order Thinking Skills in Cognitive Domain Of Revised Bloom’s Taxonomy - Nia Liska Saputri (Peneliti.net, 2021)
In 2013 curriculum , the integration of higher thinking skills are required to encourage students to achieve the competencies of critical thinking, creativity and innovation, communication, collaboration, and confidence. One of essential learning sources is textbook, therefore it should facilitate the higher thinking skills as the basis of this curriculum. As the result, this present research mainly focuses on investigating the realization of HOTS based on revised Bloom’s taxonomy namely: analyzing level (C4), evaluating level (C5), and creating level (C6) in the reading comprehension questions found within English textbooks for grade 10th which are published by the Ministry of Education and Culture entitled Bahasa Inggris SMA/MA/SMK/MAK. This research is a content analysis employing descriptive qualitative approach. The researcher collected and listed the questions in the reading comprehension tasks and then calculated the percentage and frequencies of each level of cognition. The results showed that the lower order thinking skills (LOTS) are less dominant than the higher order thinking skills HOTS). After analyzing the data, the finding of HOTS in reading comprehension questions have reached 64.3 % of 100 % while it was 35.3 % for lower order thinking skills LOTS). It indicated that this textbook concentrated more on higher –level thinking questions than lower lever thinking.